Dwelling Near in Mountains Farthest Apart: A Conversation - Barbaza, Remmon E (Archīum Ateneo, 2013)
In November 2012, Amsterdam-based Spanish visual artist Paloma Polo came to the Philippines for the initial phase of her project on land use and vulnerability. She was hosted by the Department of Philosophy at the Ateneo de Manila University, with some of whose members she began collaborating, including Remmon E. Barbaza, an associate professor of philosophy who is currently working on an interdisciplinary project on disaster risk management. Polo is currently based in Manila to develop a research project and to work on a film project on the topics mentioned earlier, and is collaborating and teaching as adjunct professor with the Center for International Studies at the University of the Philippines at Diliman, Quezon City. In this conversation, Polo and Barbaza exchange ideas on such topics as interdisciplinary work, art, philosophy, history, human agency and the necessity behind the creative impulse, in both artistic and intellectual works.